Age-Dependent Absolute Abundance of Hepatic Carboxylesterases (CES1 and CES2) by LC-MS/MS Proteomics: Application to PBPK Modeling of Oseltamivir In Vivo Pharmacokinetics in Infants - Boberg, Mikael (Drug Metab Dispos, 2017)
The age-dependent absolute protein abundance of carboxylesterase (CES) 1 and CES2 in human liver was investigated and applied to predict infant pharmacokinetics (PK) of oseltamivir. The CES absolute protein abundance was determined by liquid chromatography-tandem mass spectrometry proteomics in human liver microsomal and cytosolic fractions prepared from tissue samples obtained from 136 pediatric donors and 35 adult donors. Two surrogate peptides per protein were selected for the quantification of CES1 and CES2 protein abundance. Purified CES1 and CES2 protein standards were used as calibrators, and the heavy labeled peptides were used as the internal standards. In hepatic microsomes, CES1 and CES2 abundance (in picomoles per milligram total protein) increased approximately 5-fold (315.2 vs. 1664.4) and approximately 3-fold (59.8 vs. 174.1) from neonates to adults, respectively. CES1 protein abundance in liver cytosol also showed age-dependent maturation. Oseltamivir carboxylase activity was correlated with protein abundance in pediatric and adult liver microsomes. The protein abundance data were then used to model in vivo PK of oseltamivir in infants using pediatric physiologically based PK modeling and incorporating the protein abundance–based ontogeny function into the existing pediatric Simcyp model. The predicted pediatric area under the curve, maximal plasma concentration, and time for maximal plasma concentration values were below 2.1-fold of the clinically observed values, respectively.